On the importance of varying device thickness and temperature on the outcome of space-charge-limited current measurements - Zhao, Alfred; Le Corre, Vincent M.; Röhr, Jason A. (Frontiers in Electronic Materials, 2024)
Space-charge-limited current (SCLC) measurements are commonly employed to characterize charge-transport properties of semiconductors used in next-generation thin-film optoelectronics, such as organic 𝜋-conjugated small molecules and polymers, and metal-halide perovskites. Despite the wide-spread adoption of the method, there is no community-wide consensus around how SCLC measurements should be performed, nor how the data should be analyzed and reported. While it is common to report device characteristics by employing a simplistic analytical model for fitting a single J-V curve obtained from a solitary device at room temperaturesometimes in a very select voltage range-expectedly, such an approach will often not give an accurate picture of the underlying physics. On that account, we here aim to highlight the importance of reporting values extracted from not just a solitary single-carrier device measured at room temperature, but from devices with different thicknesses measured at varying device temperature. We also highlight how the choice of device thickness is especially critical in determining what device and material characteristics can be extracted from SCLC measurements, and how this choice can greatly affect the conclusions drawn about the probed semiconducting material. While other factors could affect the outcome of an SCLC measurement and the subsequent analysis, we hope that the topics covered in this article will result in overall improved charge-transport characterization of thin-film semiconductors and initiate a broader discussion into SCLC metrology at large.